Designing Probability Learning with Volleyball Context through a Problem-Based Learning Approach in Vocational Schools: English - Dini Pujiani; Kiki Nia Sania Effendi (MASI Mandiri Edukasi, 2025)
This study is based on the importance of applied, contextual, and relevant mathematics learning that meets the needs of the workplace and entrepreneurship. This study aims to develop a mathematics learning design for compound probability events by applying a Problem-Based Learning (PBL) model contextualized with volleyball. This study employs a design research method consisting of three stages: preliminary design, teaching experiment, and retrospective analysis, conducted at SMKN 1 Rengasdengklok, involving two classes: a small class with 12 students and a large class with 35 students from class X TJKT 1. Data was collected by recording classroom activities and group work, collecting students' work, administering achievement tests, and interviewing them. This study demonstrates that volleyball as a contextual medium fosters improved conceptual understanding of compound probability among vocational high school students. The retrospective analysis of the learning process showed that through activities linking probability to volleyball games, students developed understanding through experiences such as calculating the probability of a successful serve or the ball entering or exiting the court, facilitated through Student Worksheets with a volleyball context. Based on this research, it is recommended that the Realistic Mathematics Education (RME) approach with a volleyball context be applied in probability learning at vocational high schools.